CORRELATION OF FOLLICLE STIMULATING HORMONE AND LUTEINISING HORMONE WITH TESTICULAR SPERM BIOPSY RESULT - Ardiyansyah, Fadhil; Utomo, Trisula (Indonesian Journal of Urology, 2014)
Objective: To investigate the correlation of follicle stimulating hormone (FSH) and luteinising hormone (LH) with testicular sperm biopsy result in azoospermia patients. Material & methods: This is a cross sectional descriptive analytic study. Data were collected from medical record in Klinik Permata Hati Sardjito General Hospital Yogyakarta. We divided them into two groups, sperm group and non-sperm group of sperm biopsy result. We recorded the level of FSH and LH pre-operation. The results were expressed as mean ± standard deviation (SD). The correlation coefficient (r) between various parameters was determined by analysis for Spearman’s rank correlation test. Results: We found 35 patients who met the inclusion and exclusion criteria during 2010-2012, who performed testicular biopsy, age range between 28-44 yo. The mean of FSH on sperm group (12.75 mIU/mL) was higher than non-sperm group (7.26 mIU/mL). The mean of LH on sperm group (5.8 mIU/mL)was also slightly higher than non-sperm group (5.70 mIU/mL). We found weak correlation between FSH level and testicular biopsy (r = 0.095), while on LH level was found negative correlation with testicular biopsy (r = -0.053). There were 42.85% patients with negative sperm result within normal range of FSH and 100% with normal range of LH. The Level of FSH with positive result ranged between 1.94-19.7 mIU/mL and LH level with positive result were 1.38-17.69 mIU/mL. Conclusion: FSH and LH were important plasma hormones correlated with spermatogenesis. FSH level between 1.94-19.7 mIU/mL and LH level between 1.38-17.69 mIU/mL could be used as reliable criteria for testicular sperm biopsy.Keywords: Follicle stimulating hormone, luteinising hormone, testicular sperm biopsy, azoospermia.